Vascular complications of black patients with type 2 diabetes mellitus in Southern Brazil - Gerchman, Fernando (2008)
Ethnicity has been shown to be associated with micro- and macrovascular complications of diabetes in European and North American populations. We analyzed the contribution of ethnicity to the prevalence of micro- and macrovascular complications in Brazilian subjects with type 2 diabetes attending the national public health system. Data from 1810 subjects with type 2 diabetes (1512 whites and 298 blacks) were analyzed cross-sectionally. The rates of ischemic heart disease, peripheral vascular disease, stroke, distal sensory neuropathy, and diabetic retinopathy were assessed according to self-reported ethnicity using multiple logistic regression models. Compared to whites, black subjects [odds ratio = 1.72 (95%CI = 1.14-2.6)] were more likely to have ischemic heart disease when data were adjusted for age, sex, fasting plasma glucose, HDL cholesterol, hypertension, smoking habit, and serum creatinine. Blacks were also more likely to have end-stage renal disease [3.2 (1.7-6.0)] and proliferative diabetic retinopathy [1.9 (1.1-3.2)] compared to whites when data were adjusted for age, sex, fasting plasma glucose, HDL cholesterol, hypertension, and smoking habit. The rates of peripheral vascular disease, stroke and distal sensory neuropathy did not differ between groups. The higher rates of ischemic heart disease, end-stage renal disease and proliferative diabetic retinopathy in black rather than in white Brazilians were not explained by differences in conventional risk factors. Identifying which aspects of ethnicity confer a higher risk for these complications in black patients is crucial in order to understand why such differences exist and to develop more effective strategies to reduce the onset and progression of these complications.